2017
DOI: 10.7554/elife.30005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic up-scaling preserves motor circuit output after chronic, natural inactivity

Abstract: Neural systems use homeostatic plasticity to maintain normal brain functions and to prevent abnormal activity. Surprisingly, homeostatic mechanisms that regulate circuit output have mainly been demonstrated during artificial and/or pathological perturbations. Natural, physiological scenarios that activate these stabilizing mechanisms in neural networks of mature animals remain elusive. To establish the extent to which a naturally inactive circuit engages mechanisms of homeostatic plasticity, we utilized the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 64 publications
9
40
0
Order By: Relevance
“…As rhythm generating networks are highly sensitive to inhibition of AMPAR in this preparation (Chen & Hedrick, ; Kottick, Baghdadwala, Ferguson, & Wilson, ), we bath applied a blocker of AMPAR, DNQX, at a low concentration that did not abolish the respiratory rhythm to address its influence on the motor amplitude in control frogs and those after hibernation. We found that acute application of DNQX did not affect the amplitude of the motor output in controls; however, amplitude decreased by about half after blocking AMPAR in preparations from hibernating frogs (Figure 3b; Santin et al, ). Because blocking AMPAR reduced motor output after hibernation, but not before, these results suggest that increases in excitatory synaptic strength contribute to producing an adequate level of motor drive following winter.…”
Section: Evidence For Compensatory Forms Of Plasticity In the Respiramentioning
confidence: 70%
See 4 more Smart Citations
“…As rhythm generating networks are highly sensitive to inhibition of AMPAR in this preparation (Chen & Hedrick, ; Kottick, Baghdadwala, Ferguson, & Wilson, ), we bath applied a blocker of AMPAR, DNQX, at a low concentration that did not abolish the respiratory rhythm to address its influence on the motor amplitude in control frogs and those after hibernation. We found that acute application of DNQX did not affect the amplitude of the motor output in controls; however, amplitude decreased by about half after blocking AMPAR in preparations from hibernating frogs (Figure 3b; Santin et al, ). Because blocking AMPAR reduced motor output after hibernation, but not before, these results suggest that increases in excitatory synaptic strength contribute to producing an adequate level of motor drive following winter.…”
Section: Evidence For Compensatory Forms Of Plasticity In the Respiramentioning
confidence: 70%
“…, long‐term potentiation) are unlikely to explain the mEPSC amplitude increases in these neurons (Gainey, Hurvitz‐Wolff, Lambo, & Turrigiano, ). Notwithstanding limitations with interpreting these outcomes as truly global and multiplicative (Kim, Tsien, & Alger, ), these results provide strong evidence that a mechanism identified by the field as homeostatic for neurons can be triggered by the hibernation environment (Santin et al, ).…”
Section: Evidence For Compensatory Forms Of Plasticity In the Respiramentioning
confidence: 70%
See 3 more Smart Citations